DAMPAK MEDIA KARTU KATA BERGAMBAR BERBASIS AI TERHADAP PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN PADA MURID SEKOLAH DASAR - Jihan Nuraini Fadilah; Yudi Bachtiar; Ihsan Rizali (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to describe the current condition of second-grade elementary school students’ early reading skills before the implementation of the instructional media, analyze differences in the improvement of early reading skills between students who used AI-based illustrated word card media and those who received conventional instruction, and determine the magnitude of the media’s impact. This study was motivated by students’ varied and suboptimal early reading skills, as indicated by difficulties in recognizing and distinguishing letters and reading syllables, words, simple sentences, and short texts. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The participants consisted of 56 second-grade students at SDN Pasawahan Kidul, divided into an experimental group and a control group. The experimental group received instruction using AI-based illustrated word card media, while the control group received conventional instruction. Data were collected through an oral reading test that assessed students’ skills in reading letters, syllables, words, simple sentences, and short texts. The results showed that the initial early reading skills of students in both groups were varied and had not yet reached an optimal level. There was a significant difference in improvement between the two groups, with the experimental group showing greater improvement than the control group. The use of AI-based illustrated word card media also had a large effect on improving students’ early reading skills. Therefore, the media can be used as an engaging, adaptable, and interactive instructional alternative in elementary schools.